Immune parameters differentiating active from latent tuberculosis infection in humans. Issue 6 (December 2015) - Lee, Ji Yeon; Jung, Young Won; Jeong, Ina; Joh, Joon-Sung; Sim, Soo Yeon; Choi, Boram; Jee, Hyeon-Gun; Lim, Dong-Gyun
Summary: Tuberculosis remains a highly prevalent infectious disease worldwide. Identification of the immune parameters that differentiate active disease from latent infection will facilitate the development of efficient control measures as well as new diagnostic modalities for tuberculosis. Here, we investigated the cytokine production profiles of monocytes and CD4 + T lymphocytes upon encountering mycobacterial antigens. In addition, cytokines and lipid mediators with immune-modulating activities were examined in plasma samples ex vivo. Comparison of these parameters in active tuberculosis patients and healthy subjects with latent infection revealed that, active tuberculosis was associated with diminished Th1-type cytokine secretion from CD4 + T cells and less augmented inflammatory cytokine secretion from monocytes induced by IFN-γ than that in latent tuberculosis infection. In addition, a higher plasma concentration of lipoxin A4 and lower ratio of prostaglandin E2 to lipoxin A4 were observed in active cases than in latent infections. These findings have implications for preparing new therapeutic strategies and for differential diagnosis of the two types of tuberculosis infection.